The Impact of QRIS Convenience on Non-Cash Transaction Satisfaction: The Role of Usage as an Intervening Factor - Tricahyono, Nor Salim; Aviva, Itsla Yunisva; Hasnita, Hasnita (Universitas Ahmad Dahlan, 2024)
This research aims to analyze the impact of QRIS (Quick Response Code Indonesian Standard) convenience on non-cash transaction satisfaction among Bank Muamalat customers, with usage as an intervening factor. Employing a quantitative approach, primary data were collected via questionnaires. The data analysis utilized the Structural Equation Model (SEM) based on Partial Least Square (PLS) and path analysis techniques. The findings reveal a significant positive relationship between the convenience of QRIS and customer satisfaction with non-cash transactions at Bank Muamalat. Additionally, the study demonstrates that usage partially mediates the effect of QRIS convenience on customer satisfaction. This research contributes to the literature by examining the influence of QRIS convenience on non-cash transaction satisfaction, with a particular focus on the mediating role of usage. Understanding the pivotal role of perceived convenience in fostering customer satisfaction and loyalty allows Bank Muamalat to tailor its strategies to better meet customer expectations, thereby promoting continued use of QRIS for non-cash transactions.